Analytical simulator of proton radiography and tomography for different detector configurations - Gianoli, Chiara; Magallanes Herńandez, Lorena (Physica medica, 2019)
Purpose - An analytical simulator of ion Radiography (iRad) and Computed Tomography (iCT) for protons is proposed to serve as imaging benchmark for different detector configurations. - Methods - The analytical simulator is applied to an anthropomorphic phantom and provides iRad and iCT benchmarks. Proton trajectories are traced relying on the Most Likely Path (MLP) algorithm. To simulate the proton trajectories the Multiple Coulomb Scattering (MCS) model embedded in the MLP algorithm is extended to non-uniform water equivalent materials according to variable substitution in the well-known statistical description in uniform water. The proton trajectories are instead estimated relying on the typical assumption of uniform water, thus causing intrinsic inaccuracies of the MLP algorithm. In this work the analytical simulator is used to explore and firstly compare the imaging performances of list-mode and integration-mode detector configurations with proton pencil beam scanning. - Results - The intrinsic inaccuracies of the MLP algorithm affect the imaging performances of list-mode detector configuration, which nevertheless remains superior to integration-mode detector configuration for iCTs. For relatively higher proton statistics, comparable or better imaging performances are offered by integration-mode detector configuration for iRads (upto 29.2% of WET difference). Uncertainties of proton trajectories due to beam spot size are shown to compromise the imaging performances of integration-mode detector configuration, but also to affect the accuracy of the MLP algorithm for list-mode detector configuration. - Conclusions - Based on MCS model in non-uniform water equivalent materials, the proposed simulation environment can serve for development and testing of dedicated imaging methodologies prior to and in combination with realistic Monte Carlo simulations.
Gesehen am 06.06.2019